Improving Students’ Reading Comprehension Through The “Read, Ask, And Put” Strategy - Darmawansah; Haryanto Atmowardoyo; Andi Anto Patak (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2024)
This research aimed to improve students' reading comprehension abilities in class XI APHP B, which was considered very low and far below the school's minimum achievement standards (KKM). This research used a Classroom Action Research (CAR) method consisting of Plan, Act and Observe, and Reflect stages that applied the Read, Ask, and Put (RAP) strategy in teaching reading comprehension. The research results showed that implementing the RAP strategy into the cycles of CAR could improve students' reading comprehension abilities in the class mentioned above. In the first cycle of this research, the average student score still did not reach the target, namely only 56.29. Thanks to the evaluation and reflection carried out in the second cycle, the average student score in this cycle was able to reach 74.81, exceeding the set KKM of 72.00. This research concluded that implementing the RAP strategy in two CAR cycles succeeded in improving the reading comprehension abilities of class XI APHP B students beyond the minimum standards (KKM) that had been set. The results of this research can provide input or knowledge to teachers and students to improve their teaching and learning quality, especially in reading comprehension.